APPLYING CUE CARDS TO IMPROVE STUDENTS’ WRITING SKILL - ' Shofiyatul Huriyah (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
Abstract This study was aimed to find the use of cue cards can improve students writing ability at eleventh grade of SMAN 3 OKU. The method of this study was classroom action research consisted of three cycles. One cycle consisted of three and two meetings. It meant that were seven meetings for three cycles. This classroom action research was done at SMA Negeri 3 OKU. Subject in this study was class XI MIPA 3 Senior High School in academic year 2019-2020. The study findings indicated that the using of cue card in teaching and learning process was effective in improving the students’ writing ability. It was proved that the mean score in Cycle I was 54.24, Cycle II improved to 62.35 and Cycle III the mean of students score was 75.30. Based on the result of the study, it can be concluded that the use of cue card can improves students’ writing ability. Therefore, it is recommended that the teachers use cue card media in teaching writing. Keywords: Cue Cards, Improve, Writing Skill